DIKSI PADA KARANGAN NARASI SISWA KELAS VIII C MTs. ALKHAIRAAT KALUKUBULA - Hartati Hartati; Idrus Idrus (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2018)
This research aims to describe the findings about to the use of diction in the narrative essay and then will be used as a source of student learning. The research used qualitative method. The method of data collection is document techniques. This research was conducted by describing the use of diction, especially the accuracy of the use of diction with seven requirements for the accuracy of diction. From the results of the analysis conducted by researchers, 26 of the 13 narrative essays of students were obtained. Of the seven types of diction requirements that were analyzed found five inaccuracies in the use of diction namely 1) Synonyms words, 2) Use of general words and special words, 3) Use of connotative and denotative words, 4) Use of sense words, 5) Continuity of word choices , and from the data obtained, there are also those that are not found according to the requirements for accuracy of diction, namely 1) Abstract and Concrete Words 2) Use of foreign words and terms